Perancangan dan Analisis Performa 3D Printer Cartesian - Setyoadi, Yuris; Hermana, Rifki; Hakim, Rahman; Riyadi, Achmad Didi; Widiastuti, Hanifah (Politeknik Negeri Batam, 2023)
3D printer technology offers the capability to print 3D objects with nearly perfect accuracy, making it a crucial tool in the industry for rapid prototyping. This study employs an experimental approach to design a Cartesian 3D Printer with a printing area of X-axis 150 mm, Y-axis 150 mm, and Z-axis 200 mm, and subsequently compares the printing accuracy with the Anycubic Mega Zero 3D printer, which has a printing area of X-axis 220 mm, Y-axis 220 mm, and Z-axis 250 mm. Both machines underwent testing by printing block specimens 10 times each. The printing results revealed several specimens that did not meet the specified tolerance limits. In the Cartesian 3D Printer, three dimensional measurements exceeded tolerance levels in specimens 7 and 8, specifically in length, width, and height dimensions. Meanwhile, in the Anycubic Mega Zero 3D Printer, five measurements exceeded tolerance limits in specimens 6, 8, and 9, with one width dimension and two length and height dimensions. From these findings, it can be concluded that the Cartesian 3D Printer demonstrates higher accuracy compared to the Anycubic Mega Zero 3D Printer.